2013
DOI: 10.4067/s0718-95162013005000010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of NaCl stress on Jatropha cotyledon growth and nitrogen metabolism

Abstract: The effects of treatment with 50 and 100 mM NaCl on cotyledon growth, nitrogen assimilation, and the activities of key nitrogen metabolism enzymes were investigated in developing Jatropha curcas cotyledons. Growth inhibition was observed, and relative water content in the developing cotyledons significantly decreased in the 100 mM NaCl treatment. Lower levels of NO 3 -, NO 2 -, and NH 4 + in the cotyledons were recorded when they were supplied with 50 and 100 mM NaCl. Nitrate reductase activities decline by 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…These results indicate that the tolerance in castor cotyledons to salinity-alkalinity stress was much stronger than that in true leaves. Similar results were also found in Jatropha by Gao et al (2013). Castor cotyledon, unlike most other plants, can be retained in the seedling and does not off for more than a month during early seedling stage.…”
Section: Discussionsupporting
confidence: 84%
“…These results indicate that the tolerance in castor cotyledons to salinity-alkalinity stress was much stronger than that in true leaves. Similar results were also found in Jatropha by Gao et al (2013). Castor cotyledon, unlike most other plants, can be retained in the seedling and does not off for more than a month during early seedling stage.…”
Section: Discussionsupporting
confidence: 84%
“…1) of tomato plants. These observations were reported in many glycophytes (Saber et al, 1995, Abd El-Baki, 2000Surabhi et al, 2008;Hossain et al, 2012 andGao et al, 2013). There are several possibilities could be explained the suppression of NO -3 accumulation and NO -3 reduction, in this study, firstly, the inhibitory effect of NaCl stress on the plasma membrane integrity due to the generation of ROS (Ezzat et al, 2015) resulting in a disturbance of NO -3transporter ions such as K + and Ca 2+ as well as blocking NO -3 channels (Debouba, 2006 andWahid et al, 2007).…”
Section: Discussionsupporting
confidence: 65%
“…Many authors (Gouia et al, 1994;Hoai et al, 2005;Hossain et al, 2012 andGao et al, 2013) suggested that salinity stress resulted in a marked increase of NH +4 accumulation. In accordance with these views, noteworthy, there was a significant accumulation in foliar NH +4 content (Table 3) of tomato plants in response to NaClstress.…”
Section: Data Inmentioning
confidence: 99%
“…On the other hand, arogenate dehydratase, prephenate dehydratase, chloroplastic-like bifunctional aspartate aminotransferase and glutamate aspartateprephenate aminotransferase, cell wall-associated hydrolase, Cysteine-rich RLK (receptor kinase) 8, integrase core domain containing, Regulator of rDNA transcription 15, RNA-directed DNA polymerase homolog, probable pectate lyase 18, senescence-associated and UDP-galactose transporter 2-like transcripts that related to TEs were observed in salt-treated sample. In previous studies, it was reported that aspartate aminotransferase (AspAT) was induced during the addition of NaCl (Gao et al, 2013;Nam et al, 2012). These transcripts may have an important role in response to salt stress in P. vulgaris.…”
Section: Go Analysis Of Tes Responsive To Salt Stressmentioning
confidence: 99%